The Role of Traditional Medicines as Chemopreventive and Suppressive Agents in Cancer Treatment Deanova Insiratu - Nurul Andini; Gilang Kurniawan; Nahla Akila Fikria (Pt. Anagata Sembagi Education, 2024)
The purpose of this study was to determine the role of traditional medicine as a chemopreventive and suppressive agent in the treatment of Deanova Insiratu Cancer. This study is a qualitative study, this study will use a retrospective and prospective observational approach. Data will be collected from the medical records of patients who have used Deanova Insiratu previously, as well as from direct observation and interviews with individuals who are currently using or have experience with this traditional medicine. Research Results Cancer or malignant tumors can occur due to the growth of body tissue cells that proliferate abnormally. Cancer prevention can be done with healthy living habits and avoiding risk factors that can cause cancer. Cancer treatment can be done in 4 ways, namely by surgery, radiotherapy, immunotherapy and chemotherapy. Cancer screening can be done with mammography, ultrasonography (USG), and Magnetic Resonance Imaging (MRI). Natural ingredients that have effects as cancer prevention and help cancer treatment include Soursop leaves (Annona muricata), Celery leaves (Apium graveolans linn), Red Atai Spike leaves (Angiopteris ferox copel), Benalu Kepel (Dendrophthoe pentandra (L.) Miq.), and Tapak Dara leaves (Catharanthus roseus).